Microsoft Access-Based Accounting System Designated For Toko Indra - Jessie Fircayanthi Oh; Muhammad Taufik (ConCEPt - Conference on Community Engagement Project, 2023)
The inadequate accounting recording system implemented at Toko Indra is because transactions are recorded manually. That impact the inefficiency and irrelevance of financial reports so that it can lead to inaccuracies and completeness of reports needed for decision-making. This community service aims to create an accounting system using Microsoft Access that scopes include form, bookkeeping system, and financial reporting. The methodology data collection was obtained from observation and interview with the partner. The outputs of the accounting recording system include a list of chart of accounting, suppliers, inventory form, purchases form, sales form, general journal form, income report, and financial position report. The output would guide SMEs in knowing inventory turnover and financial conditions not only cashflows. Therefore, SMEs can make better decision making to increase sales and monitoring the inventory.